Demand for World Bank Lending - Ratha, Dilip (World Bank, Washington, DC, 2014)
Bridging the external financing gap has been an important factor in borrowing cgovernment's demand for World Bank loans. The demand for IBRD and IDA lending is positively related to an increase in debt service payments and inversely related to a borrowing country's level of reserves. These two variables explain a large part of the variation in IBRD and IDA lending commitments, not only since the Asian crisis but also during tranquil times over the past two decades. Borrowing to service debt during a crisis is consistent with the Bank's role as a lender of last resort as well as with its core development objectives, but such borrowing during tranquil times may conflict with the Bank's long-term objective of reducing poverty. That investment lending commitments are related to debt service payments implies that aid may be more fungible than previously believed. If Bank lending is fungible and there is no guarantee that a particular Bank loan is financing an identified investment project or program, a case could be made for greater use of programmatic lending (with well-defined conditionality) As developing countries become larger and more integrated with volatile international capaital markets, there is also likely to be a greater need for fast-disbursing, contingent program lending facilities from the Bank.